Clothes of the Crimean Tatars in the early years of Soviet power - Aliye Kerimova (Крымское историческое обозрение)
The article examines the process of Sovietization of the traditional costume of the Crimean Tatars in the 1920s. Researches made by scientists and ethnographers of the studied period confirms the fact of gradual loss of the national identity of the Crimean Tatar traditional costume and transition to the general Soviet type. The factors that influenced this process were: the influence of Russian and European fashion, military conditions, and the general decline of the economy in the country and the famine of the 1920 in the Crimea, the loss of traditional sewing and weaving techniques, the replacement of handmade fabrics with factory fabrics, the use of artificial dyes for dyeing threads. The well-to-do strata of the population and the elderly, in particular, those living in some parts of the foothill and southern coastal parts of the Crimea, were the least susceptible to modern fashion. The national attributes that managed to survive the longest period in the clothes of the Crimean Tatars were headdresses – fes and kalpak. The main features of Soviet clothing were simplicity, efficiency and functionality.